Sosialisasi Peningkatan Sanitasi Lingkungan Melalui Pengembangan Jamban Pengembangan Jamban Sehat Komunal di Bantaran Sungai Desa Babulu Laut - Azzahra, Audrey Yuza; Patience, Afriza Ramadhona; Kamilla, Natasya Dinna; Nur, Renisah; Sellin, Ribka Dwi; Rahmah, Rizqi Habiibah; Alisalman, Muhamad (Nawadeepa: Jurnal Pengabdian Masyarakat, 2022)
This socialization program was carried out in Babulu Laut Village, Babulu District, North Penajam Paser Regency. Babulu Laut Village has a number of problems that arise in the community, one of which is the lack of public knowledge about the importance of environmental sanitation, this can be seen from the absence of a shelter for the community to defecate. This problem will certainly have an impact on environmental pollution so there is a need for socialization activities so that people are aware of the importance of building healthy environmental sanitation. The result of program implementation is an increase in participants' understanding of the importance of improving environmental sanitation through healthy latrines. The method of implementing this activity is in the form of outreach and education through counseling.